Role of Media in the Commercialization of Contemporary Arts - Rani, Archana (Journal of Commerce and Trade, 2014)
The glory of all ancient civilization is unearthed in their ruins as a proof of artistic excellence when Architecture, Sculpture, Drawing and painting etc. were very intelligently planned in terms of aesthetics, magnificence and utility. Later, Indian art was influenced by Greek art and techniques but the mixing up of two forms did not compromise on the artistic excellence rather this combination further enhanced the richness of artistic creativity. There was a time when art adorned the wall of palaces, temples, or public places where the patrons would be the kings, religious bodies or the great and rich men in the society. At its most basic sense. Social media represent a shift in how people discover, read and share news, information and countent. Social media have become extremely popular because they allow people to connect in the online world to form relationships for personal, political and business use. Art, whether traditional or contemporary has been combined with the media forms to each the people. Here media, informs the people about the various art forms and the way it can be utilized for beautification or for any psychological influence, thus leading to its commercialization. Art of one country has reached to each and every part of the world through the help of media.